The importance of abolishing the conditions of graphic representation of the sign in the procedure of registration of non-traditional trademarks - Lučić, Sonja (Zbornik radova Pravnog fakulteta u Novom Sadu, 2022)
Traditional trademarks, such as words and images, have long been the dominant subject of trademark protection. However, the development of modern technology and new marketing methods have influenced the increase in applications for non-traditional trademark protection marks. However, the number of registered non-traditional trademarks, both national and supranational, was not large. The reason for that was the graphic display as a condition for the registration of the trademark. This requirement could not be satisfied by those non-traditional signs that are perceived by other senses, and not only by the sense of sight. The abolition of the conditions for graphic representation of the sign, on the other hand, has greatly contributed to the increase in the number of registered multimedia trademarks that can now be represented by video. On the other hand, the abolition of the conditions for the graphic representation of the sign did not open the way for the registration of olfactory, tactile and gustatory trademarks.
Keywords: Trademark, Nontraditional Trademark, Graphical Representation